Lymphaticovenous anastomosis of the caudal thoracic duct to the azygous vein: A feline cadaver study - Davies, Gillian F.; Hardie, Robert J.; Wild, Jessica L.; Loeber, Samantha J. (Veterinary surgery, 2024)
Objective The aim of this study was to describe a technique for anastomosis of the thoracic duct (TD) to the azygos vein (AV) using a microvascular anastomotic coupler (MAC) device in feline cadavers. Our hypothesis was that a TD‐AV lymphaticovenous anastomosis would be feasible in feline cadavers. Study design Cadaveric study. Animals Eight domestic shorthair feline cadavers. Methods A left paracostal laparotomy and 9th or 10th intercostal thoracotomy was performed. Contrast media was injected into a mesenteric lymph node and lymphography was used to identify the TD and its branches. The TD and AV were isolated, ligated, and divided with the aid of a surgical microscope. The TD and AV were anastomosed end‐to‐end using a 1.5 or 2.0 mm MAC. Intraoperative patency was assessed by manipulation of chyle and venous blood across the anastomosis. Mesenteric lymphography was repeated to confirm postoperative anastomotic patency. Results The TD was identified via lymphography in seven of eight cats. The anastomosis was successful and patency was confirmed via intraoperative assessment and postoperative lymphography in all cats. The median (range) duration for the dissection and anastomosis portions of the procedure was 122 (80–150) min. Conclusion End‐to‐end anastomosis of the TD to the AV using a MAC was feasible in the feline cadaver without major intraoperative technical challenges. Clinical significance Anastomosis of the TD and AV may have application as an alternative treatment for idiopathic chylothorax in cats. By directly connecting the abdominal lymphatics to the central venous system, the stimulus for collateral vessel development around the site of TD ligation may be minimized, which may prevent leakage of chyle through the more cranial lymphatics.